2021
DOI: 10.1093/eurpub/ckab028
|View full text |Cite
|
Sign up to set email alerts
|

Physical inactivity in nine European and Central Asian countries: an analysis of national population-based survey results

Abstract: Background Physical inactivity is a major risk factor for non-communicable diseases. However, recent and systematically obtained national-level data to guide policy responses are often lacking, especially in countries in Eastern Europe and Central Asia. This article describes physical inactivity patterns among adults in Armenia, Azerbaijan, Belarus, Georgia, Kyrgyzstan, Republic of Moldova, Tajikistan, Turkey and Uzbekistan. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Half of participants (about 53.3%) followed a relatively moderate PA with an average of 55 min accumulated MVPA time per day, and most of them were young women with a relatively high education, while the majority of participants in Group 1 were the middle-aged population. These findings were consistent with previous studies that found that physical activity decreased with the addition of age [ 20 , 21 ]. Both Group 3 and Group 4 had high levels of physical activity, with a mean total MVPA time of 94 and 89 min per day, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Half of participants (about 53.3%) followed a relatively moderate PA with an average of 55 min accumulated MVPA time per day, and most of them were young women with a relatively high education, while the majority of participants in Group 1 were the middle-aged population. These findings were consistent with previous studies that found that physical activity decreased with the addition of age [ 20 , 21 ]. Both Group 3 and Group 4 had high levels of physical activity, with a mean total MVPA time of 94 and 89 min per day, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Older adults' travel time decreased with age and becomes significantly limited in those aged over 75 years [14]. Older adults living alone have a lower propensity to travel than those living with their children [15,16]. Yanagihara [17] found that older adults with good physical health were more likely to drive to their destinations.…”
Section: Literature Reviewmentioning
confidence: 99%